Explore Westonci.ca, the leading Q&A site where experts provide accurate and helpful answers to all your questions. Explore a wealth of knowledge from professionals across various disciplines on our comprehensive Q&A platform. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.
Sagot :
[tex]( 3x + x ^2) - (4x^2 - 3x +(2x^2 - x - (5x^2 + 4x)))=\\
3x+x^2-4x^2+3x-(2x^2-x-5x^2-4x)=\\
-3x^2+6x-2x^2+x+5x^2+4x=\\
11x[/tex]
[tex](3x+x^2)-\{4x^2-3x+[2x^2-x-(5x^2+4x)]\}\\\\=3x+x^2-\{4x^2-3x+[2x^2-x-5x^2-4x]\}\\\\=3x+x^2-\{4x^2-3x+[-3x^2-5x]\}\\\\=3x+x^2-\{4x^2-3x-3x^2-5x\}\\\\=3x+x^2-\{x^2-8x\}\\\\=3x+x^2-x^2+8x\\\\=11x[/tex]
Thanks for stopping by. We are committed to providing the best answers for all your questions. See you again soon. Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. Westonci.ca is your go-to source for reliable answers. Return soon for more expert insights.